The global art world : audiences, markets, and museums - Belting, Hans; Araujo, Emanoel, 1940-; Buddensieg, Andrea; Internationales Forschungszentrum Kulturwissenschaften; Global future of local art museums. (2006 : Vienna, Austria); Where is art contemporary? (2006 : (Germany : Hatje Cantz Verlag, 2009)
Includes bibliographical references (p. 402-407).